If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x+4)=6x-7
We move all terms to the left:
2(3x+4)-(6x-7)=0
We multiply parentheses
6x-(6x-7)+8=0
We get rid of parentheses
6x-6x+7+8=0
We add all the numbers together, and all the variables
15!=0
There is no solution for this equation
| 3c-20+6c=10+6c | | (x-25)(x+24)=0 | | (x-25)(x+24)=6000 | | 7/2x=5/6 | | 18f-20f+18=-4f-10 | | (x-25)(x+24)=600 | | (x-25)(x+13)=325 | | 1=-1+t6 | | 19x=-12x | | 25=-2r+3 | | -9.1d+10.8=6.02-2.2d+19.96 | | 9=3(q+8) | | -h-18=18+4+4h | | -6q-1+7q=2q+14 | | 4=2/3(r-6) | | 3x+7x=-70 | | 8+14b-b=12b-8 | | 7(b+3)+5(b+9)=1 | | 7q+16=44 | | -5x+x/7=-3 | | -17=n-7/3 | | -7(y+4)=-5y-3 | | 5(4z+5)=8z+1 | | v2+16=20 | | 7(3n+5)=7n+4 | | w+10/4=4 | | 8y+5(5y-6)=16 | | 9b+2(5b-5)=13 | | 6a+4(5a-7)=15 | | (n-1)^2=0 | | 14x+67=7x+50 | | w+104=4 |